Jews and Samaritans in Joshua 24 - Schmid, Konrad (Hebrew bible and ancient Israel, 2017)
This article collects the evidence for a post-Priestly dating of Joshua 24 in the fifth century BCE and interprets the specific setting and concept of this text in the context of the contemporaneous rivalries and interactions between Jews and Samaritans. Joshua 24 opts for a theocratic constitution for all Israel. The choice of Shechem as the location for this scene shows that the North is not the exclusive, but a very prominent addressee of Joshua 24.